2006
DOI: 10.1074/jbc.m510597200
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Modulatory Element-binding Protein 1 Binds to Initiator Procaspases and Inhibits Ischemia-induced Apoptosis and Neuronal Injury

Abstract: Caspases are divided into two classes: initiator caspases, which include caspase-8 and -9 and possess long prodomains, and effector caspases, which include caspase-3 and -7 and possess short prodomains. Recently, we demonstrated that glucocorticoid modulatory element-binding protein 1 (GMEB1) interacts with the prodomain of procaspase-2, thereby disrupting its autoactivation and the induction of apoptosis. Here we show that GMEB1 is also capable of binding to procaspase-8 and -9. GMEB1 attenuated the Fas-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Nakagawa et al (2008) reported that GMEB1 is capable of binding to caspase-2, caspase-8, and caspase-9, and thus protect against apoptosis of neurons, another cell type susceptible to GC-induced apoptosis. In addition, the knockdown of endogenous GMEB1 using siRNA renders mice more sensitive to stress and leads to accelerated apoptosis in the central nervous system (Tsuruma et al 2006). GMEB1 and GMEB2 are co-modulators of GR and can modify the potency of agonists (EC 50 ) or the partial agonist activity (PAA) of antisteroids without direct changes in the binding affinity of the steroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakagawa et al (2008) reported that GMEB1 is capable of binding to caspase-2, caspase-8, and caspase-9, and thus protect against apoptosis of neurons, another cell type susceptible to GC-induced apoptosis. In addition, the knockdown of endogenous GMEB1 using siRNA renders mice more sensitive to stress and leads to accelerated apoptosis in the central nervous system (Tsuruma et al 2006). GMEB1 and GMEB2 are co-modulators of GR and can modify the potency of agonists (EC 50 ) or the partial agonist activity (PAA) of antisteroids without direct changes in the binding affinity of the steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid modulatory element-binding protein 1 and 2 (GMEB1 and GMEB2), members of the family of KDWK proteins, form a heterodimer that binds DNA and modulates the transactivation function of GR and thus GC effects (Zeng et al 2000). Furthermore, GMEB1 has been reported to be capable of binding to caspase-2, -8 and -9, and to inhibit caspase-mediated apoptosis (Nakagawa et al 2008;Tsuruma et al 2006Tsuruma et al , 2004.…”
Section: Introductionmentioning
confidence: 98%
“…Changes (p < 0.05) in expression of five genes (GME, HPK, caspase‐13, WTR and FW) are consistent with potential for a decline in apoptosis. For example, Tsuruma et al. (2006) reported that GME binds to initiator pro‐caspases and thereby inhibits apoptosis in neuronal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Changes (p < 0.05) in expression of five genes (GME, HPK, caspase-13, WTR and FW) are consistent with potential for a decline in apoptosis. For example, Tsuruma et al (2006) reported that GME binds to initiator pro-caspases and thereby inhibits apoptosis in neuronal injury. Haematopoeitic progenitor kinase is a functional component of the endogenous IkappaB kinase complex and is crucial for T-cell receptor-mediated NFkappaB activation (Brenner et al, 2005).…”
Section: Apoptosismentioning
confidence: 99%
“…30 Neural stem cells transplantation into youngadult ischemic rodents greatly reduced TUNEL þ apoptotic cells and inflammatory infiltration, further improved neurobehavioral outcomes. 31 We found that brain ischemia induced more neuronal apoptosis in aged rats compared with the young-adult rats, while NSC transplantation greatly attenuated neuronal apoptosis in both young-adult and aged rats.…”
Section: Discussionmentioning
confidence: 99%